Accuracy Of Reporting On Online Media Public.Com Viral (Frame Analysis Model on Covid 19 News in Bengkulu) - Prasetyo, Wahyu Prasetyo wahyu; Asnawati, Asnawati; Narti, Sri (Perkumpulan Dosen Muda (PDM) Bengkulu, 2021)
The purpose of this study was to find out about the accuracy of news